STUDENT’S KNOWLEDGE ABOUT LAND SUBSIDENCE IN SEMARANG CITY, INDONESIA - Aurelia Ayu Widhi Astuti; Wahyu Widiyatmoko; Yunus Aris Wibowo; Ratih Puspita Dewi; Muhammad Musiyam (Universitas Sebelas Maret (UNS), 2026)
The city of Semarang is one of the cities on Java Island's north coast that experiences land subsidence. The rate of land subsidence varies across different areas. This research aims to analyse the relationship between students' knowledge about land subsidence phenomena and the location of schools experiencing (SMAN 14 Semarang) and not experiencing (SMAN 4 Semarang) land subsidence in Semarang City. The population for this study comprises all high school students at SMA Negeri 4 Semarang (1,179 students) and SMA Negeri 14 Semarang (958 students). Sampling was conducted using the Slovin formula with a 5% margin of error, yielding 306 respondents from SMA Negeri 4 Semarang and 300 from SMA Negeri 14 Semarang. The sampling technique employed was cluster random sampling. Data collection techniques included multiple-choice tests, followed by point-biserial correlation analysis. The results of this study indicate that students at both SMA Negeri 14 Semarang and SMA Negeri 4 Semarang demonstrate a high level of knowledge about land subsidence, and the analysis indicates no significant relationship between students’ knowledge and school location in areas with different subsidence conditions in Semarang. This highlights the effectiveness of geography instruction in conveying local environmental phenomena and underscores the importance of integrating contextual, place-based examples, such as land subsidence, into geography curricula.